First report of the entomogenous fungus Cordyceps dipterigena from Peninsular Malaysia - Kiew, Ruth; Spooner, Brian (Malaysian Nature Society, 1987)
Cordyceps dipterigena Berk, Bc Br. is reported for the first time from a rubber estate in Selangor and from virgin forest in Johore, Peninsular Malaysia. In primary forest its host was a calliphorid fly.